Of grammar, words, and verses : in honor of Carlos Piera - Torrego, Esther; Piera, Carlos, 1942- (Language faculty and beyond, 2012)
This book offers new work by some major figures in the field of linguistics, addressing old debates from the perspective of current explanatory grammatical theory. These include paradigmatic relations among words, and agreeing adjectives and their grammatical source. Covering a broad range of empirical domains, the contributors of this volume examine the role of Economy in syntax and in syntactic interfaces with phonology and semantics, and their implications for processing. The evidence is taken from a great variety of languages, including Arabic dialects, Basque, Czech, Dutch, English, Frenc.